Alternativas de financiamiento de la atención médica en América Latina y el Caribe Alternatives for the financing of health care in Latin America and the Caribbean - Antonio Carlos Coelho Campino (Universidade de São Paulo, 1995)
Dada la magnitud del problema de salud en los paises de America Latina y el Caribe, el déficit de recursos financieros necesarios para proveer atención médica no se puede cubrir a través de aumentos en los precios, o adoptando medidas como pago por servicio o cobro por los costos de los servicios. Es necesario recurrir a la política fiscal. Se demuestra que es posible aumentar los recursos disponibles para la atención médica, tanto por el aumento en la recaudación de impuestos, como por la toma de decisión política de aumentar los ingresos del gobierno destinados a financiar la atención médica. Se revisa la experiencia de los Fondos de Emergencia Social y de las operaciones de cambio de deuda por salud como importantes fuentes adicionales de recursos especialmente para financiar la inversión. Dada a magnitude do problema de saúde nos países da América Latina e do Caribe, não é possível cobrir o déficit de recursos financeiros necessários para prover assistência médica através de aumentos nos preços, ou com a adoção de medidas como o pagamento por serviços ou a cobrança do custo dos serviços. Faz-se necessário recorrer à política fiscal. Foi mostrado que é possível aumentar os recursos disponíveis para assistência médica, tanto por meio do aumento na arrecadação de impostos, quanto pela tomada da decisão política de aumentar a parcela da receita do Governo, destinada a financiar a assistência médica. Foi revista a experiência dos Fundos de Emergência Social e das operações de troca de dívida por projetos na área de saúde como importantes fontes adicionais de recursos, especialmente para financiar o investimento. Latin America and the Caribbean (LAC) countries are experiencing both an economic crisis and a crisis in the public sector. As a result it is impossible to increase the amount of resources available to the health sector, unless there is a drastic restructuring of the way in which financing occurs. The measures so far referred to in the economic debate -user fees, cost recovery, privatization - at best represent partial solutions. Given the magnitude of health problem in LAC countries, they are unable to generate the amount of money needed to cover the deficit of financial resources for medical treatment. The central idea behind this article is that in order to cover the deficit of resources for medical treatment it is necessary to utilize fiscal resources. It is shown that it is possible to increase the amount of financial resources available for medical treatment either through increases in taxes and/or through an increase in the proportion of the government budget dedicated to medical treatment. Increases in taxes collected provide a feasible alternative. In some of the poor countries of Latin America and the Caribbean, the proportion of the Gross National Product that goes for the payment of taxes is well below the figure for that proportion found in developed countries. To increase the proportion of the government budget dedicated to medical treatment is a political decision that depends solely upon the discretion of the governments concerned. The potential of Social Emergency Funds and debt swaps to finance innovations in the production of medical treatment services, thus maintaining the current level to activity in the sector, is discussed.